Implementasi Metode Tilawati dalam Pembelajaran Mengenal Huruf Hijaiyah - Alfin Maskur (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
The study and discussion of this research aim to understand the planning of the tilawati method, the stages of the tilawati method, and the evaluation results of the tilawati method at TK Khodijah Malangsari. The research design employed in this study is qualitative research, and data collection methods include observation, interviews, and documentation. Meanwhile, data analysis involves triangulation, a technique that examines the authenticity of data by utilizing something outside the data for checking purposes or as a comparison to the data. The findings of this research indicate that the tilawati method is highly enjoyable as it incorporates the use of rhythmic songs in the learning process. The tilawati method serves as a guide for learning, making it easier to achieve both the quality and timing targets of the curriculum. In introducing the hijaiyah using the tilawati method at TK Khodijah Malangsari, the teachers prepare a set of learning materials through discussions. During the actual introduction of the hijaiyah, teachers utilize two approaches: the classical approach and the individual approach. For the evaluation results of the tilawati method at TK Khodijah Malangsari, it is expected that children can achieve the specified targets in the tilawati curriculum. This includes the ability to write and read the hijaiyah correctly, read the Arabic alphabet with proper pronunciation (tajwid), and master the unique sounds and melodies of the tilawati method.